Free-living nematode assemblages associated with maize residues and their ecological significance - Karuri, Hannah W.; Maina, Samuel; Nyoike, Rossa N. (My University, 2021)
Return of plant residues to the soil is a sustainable way of enhancing plant growth, health, and levels of soil quality. In Kenya, maize plant residues are the most commonly returned plant material in many agro-ecosystems. For any plant material to release nutrients into the soil, it must undergo a decomposition process that is usually affected by various organisms, especially nematodes. Despite their great contribution to the breakdown of plant organic matter, there is a dearth of information on the interaction between maize residues and free-living nematodes (FLN) in Kenya. In this respect, this study aimed to assess the inﬂuence of decomposing maize residues on FLN dynamics and the soil food web in Mwea, Kenya. The experimental plots were set up in a randomized complete block design, comprising of decomposition plots (incorporated with maize residue to a depth of 30 cm at a rate of 5 tons/hectare), while the plots unincorporated with maize residues were used as the control. Each treatment consisted of four replicates. In all, 30 FLN genera were recovered from the ﬁeld trials, whereby Acrobeles was signiﬁcantly abundant in decomposition plots in both seasons. We subsequently found that maize residues reduced the abundance of enrichment opportunist bacterivores (cp-1) relative to general opportunist (cp-2) bacterivores and fungivores. Notably, the results of the channel index showed that the decomposition of maize residues was dominated by fungal energy channels throughout the study in the two seasons. These results suggest that maize residues need to be coupled with a suitable labile organic matter. This would lead to sustainable, active, and reliable turn-over of maize residues into the soil food web ecosystems. The application of labile materials can also help to improve the population of enrichment bacterivores that are essential in the decomposition process. This study shows that the decomposition of maize residues inﬂuenced FLN composition, mainly the enrichment opportunist bacterivores whose abundance was lower.
Keywords: Decomposition; Ecological signiﬁcance; Free-living nematodes; Maize residue; Soil food web